Awareness of money laundering among workers in Pejabat Agama Islam Daerah Lipis Pahang / Abdul Hannan Mohd Salehen - Mohd Salehen, Abdul Hannan (2024)
Perceptions related to awareness of money laundering among all District Islamic Religious Offices in Lipis are crucial for enhancing awareness so that they do not engage in activities prohibited by Islamic teachings. The District Islamic Religious Offices in Lipis serve as places where family issues are resolved amicably. 3 respondent are selected from 30 people in the office. This respondent are selected by unit that have in the office. However. This research examines the responses of 3 employees working in the District Islamic Religious Offices in Lipis. Data was collected through face-to-face interviews to facilitate the data collection process. The data gathered from these interviews were transcribed to further facilitate analysis by the researcher. Based on the findings of this study, it was found that 3 out of the respondents have a relatively good understanding of money laundering. Furthermore, among the factors contributing to awareness of money laundering are understanding the concept of money laundering, religious legitimacy, and learning and access. The research findings also suggest that education on money laundering should be enhanced. Future research is encouraged to conduct studies more easily as there are many sources that can be referenced.